Electrical property of zirconium oxide nanoparticle synthesized by hydrothermal method. (2022) - Reddy Yadav, L.S.; Ramakrishnappa, T.; Pereira, John Rayan; Venkatesh, R.; Nagaraju, G.
Abstract: Nano science and technology being the most projecting area since many decades, because, of their perpetual applications in this Nano world. Electronic application of monoclinic blended structured Zirconium dioxide nanoparticles prepared by hydrothermal method at different temperatures using Zirconium oxychloride octahydrate as a raw material, aqueous NaOH as a precipitating agent and deionized water as a solvent to attain pure Nano crystalline powder. The size of the prepared nanoparticles around 50 nm and monoclinic structure of the samples was confirmed from XRD spectra. The band gap of the material was estimated by UV–Vis spectrophotometer which agrees with the decrease in the energy gap when the calcination temperature was increased, this may be due to increase in surface to volume ratio. The molecular nature of the synthesized material shows broad band near 500 cm −1 can be attributed to the vibration modes of Zr-O2 group confirming the formation of ZrO2 using fourier transform infra-red spectroscopy. Resistivity of the synthesized samples found with the voltage and current data values when plotted using origin pro and the slope of 9.63E+03 and 15.3E+03 gives the resistance of the material. Size dependent zirconia nanoparticles were produced suitably with reduction in synthesize time and energy consumption which are appropriate for large-scale fabrication.